H2S Donor and Bone Metabolism - Hao, Yanming; Wang, Hongzhen; Fang, Lingna; Bian, Jinsong; Gao, Yan; Li, Chong (Frontiers in Pharmacology, 2021)
Hydrogen sulfide (H2S) has been recognized as the third gasotransmitter, following nitric oxide and carbon monoxide, and can be described as a newly recognized signaling molecule with very potent protective actions. In recent years, a lot of research on H2S has been carried out at many levels because of novelty and versatility. Many diseases, including neurological diseases, cardiovascular diseases, inflammation, metabolic disorders, and bone metabolic diseases, have been linked to abnormal endogenous H2S functions and metabolism. Physiology and pharmacology of H2S has been studied, moreover, a large number of issues could be addressed /to advance our understanding of the biology and clinical potential of H2S in the future. H2S releasing agents (donors) have been widely used in the field. These compounds are not only useful research tools, but also potential therapeutic agents. For the study of mechanism and function of H2S, donors release H2S through different mechanisms. Although H2S releasers have biological activity, their function sometimes seems inconsistent. Moreover, donors have different H2S release capabilities, which may also lead to different effects. In addition, side effects may follow with the formation of H2S, and we have no idea whether these side effects affect the biological effect of H2S. As a result，it is necessary to study the H2S donor in detail and accurately. Research on H2S and bone metabolism has also become a hot topic. In this review, we summarize the current information about H2S donors related to bone metabolism diseases, and discuss some mechanisms and biological applications.